Assessing the usage of screen based media and screen time among adolescents in Mysuru: a cross-sectional study - Shwetha, G.; Doddaiah, Sunil Kumar; Bilimale, Anil S.; Murthy, M. R. Narayana (International Journal Of Community Medicine And Public Health, 2020)
Background: Media is one of the important parts of the life of school children, especially those aged between 13 to 17 years. It has both positive and negative impacts on children. It affects both physical and mental health; there will be a prominent impact on their studies also. Nowadays everyone has the accessibility of television, mobile, etc in India. This study mainly aims to assess the impact of screen-based media (SBM) and screen time among middle adolescents and the association of socio-demographic status with the usage of SBM. Methods: A cross-sectional study was conducted in Government and Private schools of Mysuru district from November to December 2019. The study included 180 school children between the age group of 13 to 17 years through simple random sampling. A semi-structured interview questionnaire was used. Results: Mobile formed the maximum used SBM. Out of the total screen time, time contributed by television 90.5%, mobile 95.6%, and both television and mobile 91.7% will be more followed by other SBM. The proportion of children having the screen time of maybe 3 hrs was found to be 25.6% and more than 3 hrs was 5.9% among the total study population. There is an association between SBM usage and the socio-demographic status i.e. age, type of family, father’s education, and father occupation with the statistical significance of p value <0.05. Conclusions: According to the current study, there is a high proportion of school children using SBM. So, there is a need to create awareness regarding the use of SBM and its impact on children among parents, teachers, and children.